Pentingnya Mediasi Dalam Mengurangi Kasus Perceraian Di Pengadilan Agama Banyumas - Teguh Anindito; Aris Priyadi; Arif Awaludin (Wijayakusuma Law Review, 2022)
Abstract Mediation as one of the tools that is needed in dealing with divorce cases is very important. Many divorce cases are resolved through mediation. Research conducted at the Banyumas Religious Court using normative juridical methods shows that mediation still needs to be socialized to resolve the various divorce cases that have piled up at the Banyumas Religious Court. It is necessary to overcome various obstacles in resolving cases through this mediation. Minimizing obstacles will help achieve optimal mediation. Efforts made by the Supreme Court by making Supreme Court Regulations further strengthen the role of mediation in settling cases. Abstrak Mediasi sebagai salah satu sarana yang sangat dibutuhkan dalam mengatasi kasus perceraian sangat terasa arti pentingnya. Banyak perkara perceraian yang diselesaikan melalui mediasi. Penelitian yang dilakukan di Pengadilan Agama Banyumas dengan metode yuridis normatif menunjukkan hasil bahwa mediasi masih perlu disosialisasikan untuk menyelesaikan berbagai kasus perceraian yang menumpuk di Pengadilan Agama Banyumas. Perlu diatasi berbagai hambatan dalam penyelesaian perkara melalui mediasi ini. Meminimalisir hambatan akan membantu tercapainya mediasi yang optimal. Upaya yang dilakukan Mahkamah Agung dengan membuat Peraturan Mahkamah Agung semakin menguatkan peran mediasi dalam penyelsaian perkara.